Interview – Heleieth Saffioti by herself: Genesis of “A Woman in a Society of Classes”. - Gonçalves, Renata; Branco, Carolina (Pontifícia Universidade Católica de São Paulo, 2011)
In 2008, at the occasion of the 40th anniversaryof May 1968, we interviewed Heleieth Saffioti inher large and bright apartment. The idea was tohave her tell us what she was doing that year,where she lived, what were her activities, whatwere her impressions of the period and what werethe contributions within the Social Sciences. Thememories were so many and so intense that heraccount was restricted to events ranging from1961, when she competed and won the positionof professor at UNESP in Araraquara, to 1967,year of her thesis defense, which later became thebook A Woman in a Society of Classes. We havethe privilege to present, through her uninterruptedaccount, the construction of the irreverent thoughtsof the feminist-Marxist precursor of gender studiesin Brazil. From her narrative emerges part of thesaga that led to the consolidation of the SocialSciences in the country.